Subsidising innovation outside or within firms' existing knowledge base: Which is best for radical innovation? - Mauricio Perez-Alaniz; Helena Lenihan; Justin Doran; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Public financial support for firm-level Research and Innovation (R&I) can generate important socio-economic returns. This is especially true if firms use this support to develop radical innovation, defined as new-to-market goods and services. However, radical innovation is risky, and prone to failure. Therefore, subsidising radical innovation can also generate sub-optimal socio-economic returns (i.e. policy failure). Understanding how public funding for R&I can be allocated in a way that encourages radical innovation, while avoiding policy failure, is crucial. Our paper investigates, for thefirst time, whether public fundingfor R&I generates more radical innovation in firms seeking to innovate by engaging in knowledge areas that are new to them, versus firms seeking to exploit their existing knowledge base. We make this distinction by using a novel approach, based on the knowledge challenges that firms face when innovating. By merging firm-level survey data with administrative data on public funding for R&I in Ireland, we find that subsidising firms seeking to engage in new knowledge areas, can result in more radical innovation and turnover from radical innovation, compared to firms seeking to exploit their existing knowledge base. These are critical insights from theoretical and policymaking perspectives, regarding the allocation of public funding for R&I.
Keywords: D3; D83; O31; O32; O33; 330; radical innovation; public financial support; knowledge base; policy failure; additionality